Persepsi Masyarakat Lokal terhadap Ekowisata Mangrove Kuri Caddi Desa Nisombalia Kabupaten Maros - Muhammad Arhan Rajab; Shermina Oruh; Andi Agustang (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2021)
The aims of this research are 1). to determine the local community's perception of the development of mangrove ecotourism in Kuri Caddi; 2). To provide a solution to the community-based Kuri Caddi mangrove ecotourism development policy formulation. The method in this study is a qualitative research with an interview method approach using a questionnaire. The results of this study are 1). The local community's perception of the Kuri Caddi mangrove ecotourism, Nisombalia Village, Maros Regency, namely the aspect of community knowledge of mangrove ecotourism reached 74% stating they already knew about mangrove ecotourism, community attitudes towards mangrove ecotourism obtained 70% agreed, community behavior towards mangrove ecotourism obtained 7% always and 51% sometimes and the use of mangrove ecosystems in people's lives gets 13% and 43% sometimes. This shows the support of the local community of Kuri Caddi for the development of mangrove ecotourism in Kuri Caddi, Nisombalia Village, Maros Regency. 2). Recommendations for the development of mangrove ecotourism in Kuri Caddi, Nisombalia Village, Maros Regency, are community-based mangrove ecotourism. The implications of this research can be used as a reference in the formulation of community-based mangrove ecotourism policies.